CHARACTERISTICS OF STUDENT’S SOCIAL PERCEPTION (GENDER ASPECT) - Demianiuk, Olena; Kosareva, Oksana (PSYCHOLOGICAL JOURNAL, 2018)
The article highlights the gender features of social perception of student youth. Today, the problem is topical because both sexes are increasingly engaged in activities that were previously closed to them because of certain social stereotypes of “male” and “female” roles distribution. It leaded to inevitable conflicts; thus, prevention and resolution of them requires knowledge of gender psychology. The development of this issue is important due to the necessity of overcoming numerous gender stereotypes prevalent in the modern world. They form rigid thinking and behaviour of males and females. Generally, the term “social perception” means how people think about other people, how they form impressions, draw conclusions, and try to explain other people’s behaviour. The content of the concept includes the perception of not only external but also internal characteristics of an object, namely intentions, thoughts, abilities, emotions, attitudes, values, etc. The study was conducted in Rivne State University of Humanities. The total number of students took part in the study – 60 people (30 boys and 30 girls), the students of the third, fourth, and fifth courses of full-time education. The age of the subjects was from 19 to 23 years. We used the Bem Sex Role Inventory (BSRI) to identify gender manifestations in person’s behaviour. For the direct study of gender differences in social perception, we used the method of examining witnesses by Anatoliy Koni (Option 2 “Clothes”) and “The Questionnaire for Gender Settings and Stereotypes”. Our study proved the connection between femininity, masculinity, androgyny and social perception. We found that social perception is better developed in persons with feminine qualities and quite well formed in androgynous persons. Masculine persons, according to the results of our study, showed a lower level of social perception development in most cases. Gender stereotypes appeared to be quite common among students; the most common for both sexes is the one, according to which a man should be the paterfamilias. Both sexes demonstrated gender social stereotypes and settings, which, on the one hand, are based on gender peculiarities and, on the other hand, are supported by social environment. They lead to deeper gender differences in the perception of the world around, which in turn may lead to misunderstandings and conflicts between males and females. Key words: social perception, gender stereotypes, student youth.